Collaborative Professional Development to Support Inclusive Instruction. Issue 3 (August 2022) - Toews, Samantha Gross; Zagona, Alison
Providing successful inclusive learning environments for students with significant support needs (SSN) requires the natural integration of supports and individualized instruction into typical general education classrooms. In co-taught, inclusive classrooms, it is important that both general and special educators know how to support learning for all students with and without SSN. Collaborative professional development (CPD) has the potential to better support the implementation of inclusive practices, as educators may share their different areas of expertise by teaching each other their most impactful instructional strategies. The following article outlines a four-step CPD cycle that can guide teachers through multiple rounds of collaborative learning in which they support each other to learn new, high-impact teaching strategies. This CPD builds off research on effective professional development strategies, including the use of role-playing and practice-based feedback. Templates and examples are provided to support the implementation of this CPD cycle.